Multiferroic behavior of gd based manganite - Sagar, S.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Ferroelectrics, 2009)
Here we report the multiferroic nature of charge ordered manganite Gd0.5Sr0.5MnO3 for the first time. The temperature variation of dielectric constant shows broad relaxor type ferroelectric transition at around 210K and magnetization measurements shows weak ferromagnetism at 50K. The dielectric peak is very close to charge ordering temperature which is an evidence of the link between electronic state and increase of dielectric response. Butterfly variation of capacitance with voltage confirms ferroelectric nature of the sample at room temperature.
Keywords: dielectric constant; manganite; Multiferroic

Colossal thermoelectric power in Gd-Sr manganites - Sagar, S.; Ganesan, V.; Joy, Pattayil Alias; Thomas, Senoy; Liebig, A.; Albrecht, M.; Anantharaman, Maliemadom R. (EPL, 2010)
Manganites belonging to the series Gd(1-x)Sr(x)MnO(3) (x=0.3, 0.4 and 0.5) were prepared by wet solid-state reaction and their thermoelectric power was evaluated. Thermoelectric power measurements revealed a peak value at similar to 40 K. All the samples exhibited a colossal thermopower at similar to 40K and in that Gd(0.5)Sr(0.5)MnO(3) exhibited a maximum value of similar to 35 V/K, which is the largest reported for these class of materials at this temperature. Temperature-dependent magnetisation measurements showed that the samples exhibit a phase transition from paramagnetic to spin-glass-like state at these temperatures. Plausible mechanisms responsible for the observed colossal thermoelectric power in Gd-Sr manganites are discussed. Copyright (C) EPLA, 2010